Buddhism and global Peace: Perspectives on Cultural Geography - Jnawali, Damodar (The Third Pole: Journal of Geography Education, 2009)
Present paper deals with the major principles of Buddhism and its need for maintaining global peace. The concept of philosophy, Buddha as an Incarnation of Vishnu, origin and evolution of Buddhism and its spatial diffusion, the Buddhist Councils, major Schools of Buddhism, and Buddha's Teachings for global peace are the major areas of discussion in this paper. Buddha's Teachings provide many practical techniques that are useful for calming anger, controlling desire and creating harmonious relationships. Present world is full of violence and corruption. People are in need of comfort that comes from a spiritual path and teaches nonviolence, contentment, compassion, generosity of spirit, and peace of mind. Buddhism teaches us to cultivate peace in our hearts and work to relieve the sufferings of all living beings. Peace at national as well as global level can be possible only if we apply Buddhism in our daily life. DOI: http://dx.doi.org/10.3126/ttp.v5i0.1950 The Third Pole, Vol. 5-7, PP 28-36:2007